Pendampingan Pengemasan Keripik Singkong untuk Meningkatkan Nilai Jual Produk UMKM - Suci Dea Ananda; Anna Fitri Ardana; Serli Meilinda; Nisiria Muniroh; M. Muhammad Beta Fathir Rahim; Maharani Maharani; Dena Ristika; Wira Alvio (Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening household and rural economies. However, many food-based MSMEs still face challenges in product packaging, resulting in limited competitiveness and suboptimal selling value. This community service activity aimed to enhance the selling value of cassava chips through packaging innovation assistance for women-led MSMEs in Alai Selatan Village. A participatory descriptive approach was employed, including initial observation, theoretical counseling on packaging functions, label design training, practical repackaging using standing pouch packaging, mentoring, and evaluation. The findings showed significant improvement in product appearance, completeness of labeling information, and partners’ understanding of packaging as a marketing strategy. The innovation contributed to enhanced perceived quality and increased entrepreneurial motivation. Packaging improvement proved to be a simple yet strategic intervention in strengthening product competitiveness. The program implies that technical assistance in packaging innovation can become an effective empowerment model for rural MSMEs to improve sustainability and market expansion.